Analysis of Foundation Organization Dynamics in Advancing Community Education - Nursanti, Erni Arum; Ansori, Ansori (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2024)
The background of analyzing the dynamics of foundation organizations in advancing community education lies in the increasing need for effective mechanisms to address societal educational challenges. By scrutinizing the operational dynamics of such organizations, insights can be gained into their pivotal role in shaping community educational landscapes. Understanding these dynamics is crucial for devising strategies that optimize their contributions to enhancing societal learning outcomes. This study analyzes the dynamics of foundation organizations in efforts to enhance community education. Using a descriptive-analytical approach, researchers identify the main challenges faced by foundations in this context. The research method involves analysis of relevant literature sources. The findings indicate that factors such as resource management, leadership, and community involvement influence the effectiveness of foundations in advancing community education. These findings offer valuable insights for practitioners and policymakers to improve the performance of foundation organizations in supporting community education. To enhance their impact, recommendations include improvements in management strategies, increased community participation, and enhanced collaboration with relevant stakeholders. This research significantly contributes to understanding the role of foundation organizations in strengthening the community education systemKeywords: Foundation Organizations, Community Education, Analytical Dynamics, Organizational Impact